Robust trajectory tracking for a feedback linearizable nonlinear system. Issue 18 (2016) - Turetsky, Vladimir
Abstract: For a nonlinear system, affine in the control and in the disturbance, a generalized tracking problem is considered. The prescribed trajectory and prescribed discrete points should be tracked robustly with respect to a disturbance bounded in L 2 It is assumed that the system has the full relative degree both with respect to the control and to the disturbance. Once the system is feedback linearized, the previous results on a robust tracking for a linear system are applied. The tracking condition is formulated in terms of an original system. Illustrative examples are presented.